Witch camps and witchcraft discourse in Africa: critiquing development practice - Mabefam, Matthew Gmalifo (Lexington Books, 2023)
Introduction: 'Witches Are Falling From The Sky': Problematising Witchcraft Beliefs and Practices In Africa -- Who is a Witch? Judgement, Facts, Truths and Knowledge -- After Judgment: Experiences of Navigating Life in Communities of Refuge -- Limitless Opportunities for Wealth? Witchcraft/Occult as a Strategy for (In)Equality and Economic (Dis) Empowerment -- Intervening in 'Witch Camps': A Contestation and Controversy -- Conclusion: Decolonisation of Development Epistemes, Knowledge, and Practices.